ANKRD11 pathogenic variants and 16q24.3 microdeletions share an altered DNA methylation signature in patients with KBG syndrome. Issue 9 (28th November 2022) - Awamleh, Zain; Choufani, Sanaa; Cytrynbaum, Cheryl; Alkuraya, Fowzan S; Scherer, Stephen; Fernandes, Sofia; Rosas, Catarina; Louro, Pedro; Dias, Patricia; Neves, Mariana Tomásio; Sousa, Sérgio B; Weksberg, Rosanna
Abstract: Pathogenic variants in ANKRD11 or microdeletions at 16q24.3 are the cause of KBG syndrome (KBGS), a neurodevelopmental syndrome characterized by intellectual disability, dental and skeletal anomalies, and characteristic facies. The ANKRD11 gene encodes the ankyrin repeat-containing protein 11A transcriptional regulator, which is expressed in the brain and implicated in neural development. Syndromic conditions caused by pathogenic variants in epigenetic regulatory genes show unique patterns of DNA methylation (DNAm) in peripheral blood, termed DNAm signatures. Given ANKRD11's role in chromatin modification, we tested whether pathogenic ANKRD11 variants underlying KBGS are associated with a DNAm signature. We profiled whole-blood DNAm in 21 individuals with ANKRD11 variants, 2 individuals with microdeletions at 16q24.3 and 28 typically developing individuals, using Illumina's Infinium EPIC array. We identified 95 differentially methylated CpG sites that distinguished individuals with KBGS and pathogenic variants in ANKRD11 ( n = 14) from typically developing controls ( n = 28). This DNAm signature was then validated in an independent cohort of seven individuals with KBGS and pathogenic ANKRD11 variants. We generated a machine learning model from the KBGS DNAm signature and classified the DNAm profiles of four individuals with variants of uncertain significance (VUS) in ANKRD11 . We identified an intermediate classification score for an inherited missense variant transmitted from a clinically unaffected mother to her affected child. In conclusion, we show that the DNAm profiles of two individuals with 16q24.3 microdeletions were indistinguishable from the DNAm profiles of individuals with pathogenic variants in ANKRD11, and we demonstrate the diagnostic utility of the new KBGS signature by classifying the DNAm profiles of individuals with VUS in ANKRD11 .